Основні види, напрямки діяльності та роль комітетів (комісій) парламенту у зарубіжних країнах - Зозуля, О. І.; Zozulia, O. I.; ORCID: http://orcid.org/0000-0002-5428-4622 (Форум права. – 2018. – № 5. – С. 38-49, 2018)
Виконано аналіз конституційно-правового статусу комітетів (комісій) парламенту у зарубіжних країнах. Встановлено, що загальною рисою парламентаризму у зарубіжних країнах є формування виключно або переважно з членів парламенту комітетів (комісій) всієї палати, спільних комітетів (комісій) двох палат, а також головних, "галузевих", спеціальних та інших комітетів (комісій) палати або всього парламенту як його робочих органів, що здійснюють нормопроектні, контрольні та інші повноваження, а в деяких країнах самостійно виконують певні функції законодавчої влади. Обґрунтовано, що для України та більшості демократичних країн з розвиненим парламентаризмом найбільш оптимальною є сильна система комітетів та/або комісій. Посилення ролі парламентських комітетів в Україні має спрямовуватись на розширення конституційного регулювання їх статусу, збільшення законодавчих і контрольних повноважень, посилення взаємодії з урядом, продовження роботи ключових комітетів у міжсесійний період, активізацію комітетських слухань, деталізацію процедури роботи, посилення інформаційних прав комітетів та забезпечення прозорості їх діяльності.

The analysis of the constitutional-legal status of committees (commissions) of parliament in foreign countries is made. It has been determined that the following types of committees and commissions are in the bicameral parliaments: committees (commissions) of the whole chamber, committees (commissions) of the chamber and joint committees (commissions) of two chambers. Committees and commissions of the chamber in its organization and functions, in general, are similar to the committees and commissions of the unicameral parliament, but they focus on ensuring activity is not so much the parliament as a whole, but the chambers. In some countries, joint committees (commissions) or other leading (main, major) committees/ commissions of the chamber or unicameral parliament may acquire special powers beyond the strictly preparatory and subsidiary provision of parliamentary activity. In foreign countries, as in Ukraine, parliamentary committees and/or commissions in its constitutional-legal status are the inter-parliamentary bodies of the parliament, according to which they are usually subordinate, responsible and accountable only to the parliament. It has been determined that the common feature of parliamentary in foreign countries is the formation exclusively or mainly from the members of parliament committees (commissions) of the whole chamber, joint committees (commissions) of two chambers, as well as the main, major "branch", special and other committees (commissions) of the chamber or the whole parliament as its working bodies, which carry out normative design, control and other powers, and in some countries independently perform certain functions of the legislature. It is substantiated that for Ukraine and the majority of democratic countries with developed parliamentary the strongest system of committees and/or commissions is seen as the most optimal. In particular, the strengthening the role of parliamentary committees in Ukraine is primarily intended to provide for the extension of constitutional regulation of its status, increase of its legislative and control powers, strengthening of interaction with government, continuation of work of key committees in the inter-session period, intensification of committee hearings, detailing of the procedure of work, strengthening guarantees of activity (information rights) committees and provide real transparency in its activities.

Выполнен анализ конституционно-правового статуса комитетов (комиссий) парламента зарубежных стран. Установлено, что общей чертой парламентаризма в зарубежных странах является формирование исключительно или преимущественно из членов парламента комитетов (комиссий) всей палаты, совместных комитетов (комиссий) двух палат, а также главных, "отраслевых", специальных и других комитетов (комиссий) палаты или всего парламента как его рабочих органов, осуществляющих нормопроектные, контрольные и другие полномочия, а в некоторых странах самостоятельно выполняющих определенные функции законодательной власти. Обосновано, что для Украины и большинства демократических стран с развитым парламентаризмом наиболее оптимальной является сильная система комитетов и / или комиссий. Усиление роли парламентских комитетов в Украине должна направляться на расширение конституционного регулирования их статуса, увеличение законодательных и контрольных полномочий, усиление взаимодействия с правительством, продолжение работы ключевых комитетов в межсессионный период, активизацию слушаний в комитете, детализацию процедуры работы, усиление информационных прав комитетов и обеспечения прозрачности их деятельности.
Main types, directions of activity and role of parliament committees (commissions) in foreign countries
Зозуля, О. І. Основні види, напрямки діяльності та роль комітетів (комісій) парламенту у зарубіжних країнах [Електронний ресурс] / О. І. Зозуля // Форум права. – 2018. – № 5. – С. 38-49. – Режим доступу : http://forumprava.pp.ua/files/038-049-2018-5-FP--Zozulia_6.pdf.
Зозуля, О. І. (2018). Основні види, напрямки діяльності та роль комітетів (комісій) парламенту у зарубіжних країнах. Форум Права, 53(5). 38–49. DOI: http://doi.org/10.5281/zenodo.2527928.
Zozulia, O. I. (2018). Osnovni vydy, napryamky diyalʹnosti ta rolʹ komitetiv (komisiy) parlamentu u zarubizhnykh krayinakh [Main Types, Directions of Activity and Role of Parliament Committees (Commissions) in Foreign Countries]. Forum Prava, 53(5). 38–49. DOI: http://doi.org/10.5281/zenodo.2527928.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; конституційно-правовий статус; конституционно-правовой статус; constitutional-legal status; Україна. Ukraine. Украина; зарубіжні країни; зарубежные страны; зарубіжний досвід; зарубежный опыт; foreign experience; комітети палати; chamber committees; комитеты палаты; парламент; parliament